Es blitzt schon wieder – dieses Mal bei aš-Šarīf al-Murtaḍā - Wagner, Ewald (Oriens, 2015)
Aš-Šarīf al-Murtaḍā (d. 1044) included in his Dīwān nine poems on the lightning. Although he removed in these poems the lightning scene from its classical position in the polythematic qaṣīda, he maintained in most of them its combination with the motif of remembrance. So, his poems are not completely monothematic like the “modern” descriptive (waṣf) poems. Also, in some other respect, the Šarīf combines the old with the new. Seven of the poems are interpreted in the article.